Beauty Construction on Clean&Clear Foaming Face Wash Video Advertisement: A Semiotic Analysis - Haryati; Deni Apriadi (UIN Salatiga, 2024)
The study attempts to explain and describe the semiotic process and the stereotype about beauty construction in video advertisements. A triadic meaning of semiotics is used to identify and analyze the data, focusing on representamen, object, and interpretant. In addition, this study also uses the theory of beauty stereotypes to identify cultural conflicts in the form of beauty construction in society. The method of this study is descriptive qualitative because the writer collected the data in the form of written words, which produces descriptive information. There are sixteen pictures captured from the